Remote sensing and Geographic Information System (GIS) applications in transport geography studies: تطبيقات الاستشعار عن بعد ونظم المعلومات الجغرافية في دراسات جغرافية النقل - Fakhruddin Ahmed Abdullah Mohammed, Jamila Omar Ibrahim Madani, Muddathir Adam Al-Nur Ibrahim (Journal of engineering sciences and information technology, 2017)
This study is to determine the learning outcomes programs of remote sensing and geographic information systems, and their role in job opportunity and work markets in Kingdom of Saudi Arabia, globally (Canada), The study illustrated the top five skills which required for success in professional life majoring in geographic information systems and mentioned by Environmental Systems Research Institute (ESRI), USA. The study deal with descriptive, analytical and comparative approaches. The study recommended the top five skills that required succeeding in Remote sensing and GIS" career, which recommended by Environmental Systems Research Institute, as the main scale to determine learning outcomes of remote sensing and geographic information system in Kingdom of Saudi Arabia and Arab world and then to identify the activities, skills and courses (i.e., the number of theoretical and practical hours, teaching methods, and laboratories ...), which are taught in these programs.